MODEL REKLAMASI PANTAI SECARA BERKELANJUTAN KASUS : PANTAI KOTA MAKASSAR - Yurnita Andi; Slamet Trisutomo; Mukti Ali (TATALOKA, 2017)
Coastal urban phenomenon in the form of high population growth, rapid economic development and inadequate control of the sea, resulting in the use of the sea and coastal regions become more intensive in the last few years. This development led to the expansion of the city was further intensified by the coastal reclamation. Reclamation has been performed in many cities of the world and also in Indonesia, but many constraints. Research on model of sustainable Reclamation is still rare. The purpose of this paper is to formulate a model that could be applied on a coastal reclamation area using an index of sustainability. This research began with literature study of previous researches of developing sustainability index that not focusing yet on coastal reclamation area with the analytic hierarchy process (AHP) and expert choices. Reclamation sustainability index is used to as a tool to develop a sustainable reclamation model. This model will help project of reclamation activities and its relationship with suitable measures to manage the implementation of a sustainable reclamation. Formulation of the model is done by analysis of Structural Equatian Model (SEM) on the Makassar coastal zone and then tested the feasibility to found the appropriate reclamation model.